Space-Frequency Grouping Based Key Extraction for Mimo-Ofdm Systems - Topal, Ozan Alp; Özbek, Berna; Karabulut Kurt, Güneş; Özbek, Berna (IEEE, 2017)
Latest developments in wireless communication networks push the limits of conventional security methods. Security can be improved with a secret key that is dynamically generated based on the surrounding physical environment. With this objective, physical layer security approaches can be implemented by means of simple signal processing methods. In this paper, we propose novel key extraction approaches based on spatial and frequency characteristics of the wireless environment. In a 2x2 MIMO-OFDM system, low key disagreement rates and key error rates are observed, proving the potential of physical layer key extraction techniques.
International Symposium on Wireless Communication Systems (ISWCS) -- AUG 28-31, 2017 -- Bologna, ITALY
Keywords: MIMO-OFDM; Physical layer security; Key error rate; Key disagreement rate; Secret key extraction